The Durability of Cognitive Behavioral Therapy for Insomnia in Patients with Chronic Pain. (9th August 2012) - Jungquist, Carla R.; Tra, Yolande; Smith, Michael T.; Pigeon, Wilfred R.; Matteson-Rusby, Sara; Xia, Yinglin; Perlis, Michael L.
Abstract : The purpose of this study was to assess the long-term (six months) effects of cognitive behavioral therapy for insomnia (CBT-I) in patients with chronic pain. The results of the pre-post treatment effects have been reported previously. The therapy was delivered by an advanced practice nurse in a research setting using a parallel-group, randomized, single blind trial of CBT-I with a contact/measurement control condition. Outcomes included sleep diary, the Insomnia Severity Index, the Multidimensional Pain Inventory, the Beck Depression Inventory, the Profile of Mood States-short form, and the Pain Disability Index. Measurement time points were end-of-treatment, three-month and six-month posttherapy. Subjects receiving CBT-I( n = 19 ), as compared to control subjects( n = 9 ), did not exhibit any significant group by visit effects on measures of sleep, pain, mood, or function after end of treatment. However, subjects in the treatment group exhibited statistically( P = 0.03 ) and clinically significant improvement in total sleep time (23 minutes) over the six months following treatment. In this paper, cognitive behavioral therapy directed to improve insomnia was successfully delivered to patients with moderate-to-severe chronic pain and the positive effects of CBT-I continued to improve despite the presence of continued moderate-to-severe pain.